ZnO nanoparticles functionalized SWCNTs as highly sensitive SERS substrate for heavy metal ions detection. (October 2022) - Parveen, Shama; Saifi, Shabeena; Akram, Shumaila; Husain, Mushahid; Zulfequar, Mohammad
Abstract: This report presents the most effective and novel approach to fabricate a three-dimensional (3D) Surface-Enhanced Raman Scattering (SERS) substrate for detection of heavy metal ions in the environment. Firstly, Single Wall Carbon Nanotubes (SWCNTs) are synthesized by Plasma Enhanced Chemical Vapor Deposition (PECVD) technique at low temperature. Then, the surface of SWCNTs is functionalized by Zinc Oxide nanoparticles (ZnO NPs) using thermal evaporation technique to achieve ZnO@SWCNTs nanocomposite film as a SERS substrate. The ZnO@SWCNTs with 3D nanostructure increases the coverage of plasmonic nanostructure. The effect of intertube and interparticle coupling generates the multitude 'hot spots' with a strong SERS effect. Different characterization techniques- Field Emission Scanning Electron Microscope (FESEM), X-Ray Diffraction (XRD), UV–Vis and Raman spectroscopy were performed. For detection of heavy metal ions, the Raman spectra are recorded for samples of different metal ions- Pb 2+, Hg 2+, Cd 2+, Cu 2+, and As 2+ . The proposed substrate demonstrates high sensitivity, selectivity and very low Limit of detection of the order of 0.225 nM with high stability and repeatability for Pb 2+ . Therefore, the proposed ZnO@SWCNTs nanocomposite SERS substrate can be used as a powerful tool for the detection of heavy metal ion- Pb 2+ in aqueous solutions for a green environment.